Answer:
8/16, 12/24, 16/32, and 20/45
Step-by-step explanation:
1. (54/9)6 equation
6 x 6
36 answer
Question 7: Choose the correct simplification of the expression (3x − 6)(2x2 − 4x − 5)
Answer:
7. 6x³ - 12x² + 12x + 15
Step-by-step explanation:
(3x-6)(2x² - 4x - 5)
3x • 2x² = 6x³
3x • -4x = -12x²
3x • -5 = -15
-6 • 2x² = -12x²
-6 • -4x = 24x
-6 • -5 = 30
combine terms
6x³ - 12x² - 15 - 12x² + 24x + 30
combine like terms
6x³ - 24x² + 24x + 15
hope this helps :)
in the future, only ask one question per brainly submission. thanks!
5 10 15 20 25 30 35 40 45 50 55 60 65 70 75 80 85 90 95 100 105 110 115 120
8 16 24 32 40 48 56 64 72 80 88 96 104 112 120 128 136 144 152 180
Simplified 3/4